Analysis of apoptosis in peripheral blood cells from breast and ovarian cancer - Kulig, Andrzej; Smolarz, Beata; Kozłowska, Elżbieta; Romanowicz-Makowska, Hanna; Mankiewicz, Joanna; Szyłło, Krzysztof; Zadrożny, Marek; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2002)
Purpose: Apoptotic cell death plays a central role in the pathogenesis and disease progression of cancers. In present work we investigated the association between presence of apoptotic peripheral blood cells and breast and ovarian cancer progression. Materials and methods. The apoptosis was analysed in blood cells of breast (n = 22) and ovarian cancer patients (n = 19). Blood samples from age matched healthy women served as control (n = 20). The apoptotic peripheral blood cells were detected by agarose gel electrophoresis. Results. The apoptotic cells were identified in 82% (18/22) of the breast cancers and in 63% ovarian cancer patients (12/19). The number of positive samples were significantly higher among cancer samples than among control samples (P 0.05) in presence of apoptosis between subgroups assigned to histological stage. Conclusion. The high frequency of apoptotic peripheral blood cells in breast and ovarian tumours suggests a potential role of apoptosis in cancers appearance and/or progression.